P-functional phosphaalkenes with C-isopropyldimethylsilyl groups, and a sterically stabilized P-cyano phosphaalkene. (3rd March 2016) - Nemes, Delia R.; Bîrzoi, Roxana M.; Hrib, Cristian; Jones, Peter G.; Bartsch, Rainer; du Mont, Wolf-W.
GRAPHICAL ABSTRACT: ABSTRACT: The dehydrochlorination of the dichlorophosphane (iPrMe2 Si)2 C(H)PCl2 (2 ) with 1, 4-diazabicyclo[2.2.2]octane (DBO) provides the P-chlorophosphaalkene (iPrMe2 Si)2 C=PCl (3 ). Halide exchange reactions of3 with AgBF4, with Me3 SiBr, and with Me3 SiI lead to the P-halogenophosphaalkenes (iPrMe2 Si)2 C=PX (X = F:4 ; X = Br:5 ; X = I:6 ). From the reaction of3 with AgCN, the sterically stabilized P-cyanophosphaalkene (iPrMe2 Si)2 C=P-CN (7 ) was isolated. The structures of the related P-fluorenylphosphaalkene9 (from3 with fluorenyllithium) and of the P-selenophosphaalkenes (iPrMe2 Si)2 C = PSe(2, 4, 6-tBu3 C6 H2 ) (10 ) and [(iPrMe2 Si)2 C=P]2 Se (11 ) were determined by X-ray crystallography.